Composition, cellularity and biochemical profile of milk from primiparous and pluriparous Holstein cows during the stages of lactation - Alves, D. D. [UNESP]; Silva, D. G. [UNESP]; Aguiar, G. A. [UNESP]; Nogueira, G. S. [UNESP]; Silva, M. F.; Leite, R. V. R. S. [UNESP]; Lacerda-Neto, J. C. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2025)
The aim of the study was to verify the influence of calving order and stage of lactation on milk composition, SCC and biochemical profile of whey from Holstein cows. Two hundred negative milk samples in strip cup test and in CMT and with SCC < 200,000 cells/mL were allocated into three groups: milk samples from females with one lactation (G1; n=76), milk samples from females with two or three lactations (G2; n=73) and milk samples from females with four to six lactations (G3; n=51) according with the phase of lactation (initial, intermediate and final). GGT and ALP activities, and total protein, albumin, total Ca, P, Mg, Fe, Cl, Na, K and ionized Ca concentrations were determined. There was an influence of calving order and stage of lactation on SCC in all groups, while milk composition (fat, protein, lactose and total solids) was influenced only by order of calving. The lactation stage influenced all biochemical parameters evaluated of whey. Calving order also influenced biochemical profile, except the iron concentration. More detailed knowledge of the physiological variations that influence milk composition can contribute to the establishment of more accurate and specific ranges of normal values to monitor the health of mammary gland.
Keywords: SCC; CMT; stage of lactation; calving order; whey